Results of Two-Years Mammographic Screening in the Kaluga Region - K. S. Drzhevetskaya; G. P. Korzhenkova (Вестник рентгенологии и радиологии)
Objective: approbation of the project of mass breast cancer mammographic screening in the Kaluga Region.Material and methods. From April 2018 to December 2019, screening mammography was performed in 35,439 women aged from 38 to 93 years (mean age 57.33 ± 8.07 years). The study was carried out on mobile mammography complexes assembled on Russian KamAZ vehicles with Russian-made equipment from Amiko company. Mammography was performed in frontal and oblique projections. BI-RADS ACR international classification was used to standardize the identified changes and assess the sensitivity and specificity of the study method.Results. Out of the total number of women examined, pathological changes (BI-RADS IV–V) were assumed according to mammography data in 778 (2.2%) cases, of which 700 (1.98%) patients appealed to an oncological institution. Benign processes were found in 394 (1.11%) patients, breast cancer in 164 (0.46%). Without verification of the diagnosis, 137 (0.39%) patients remained under the supervision of oncologists. Distribution of detected tumors by stages for 2 years of observation: stage 0 – 7, stage 1 – 73, stage 2 – 56, stage 3 – 13, stage 4 – 3. The stage was not set in 4 cases. The total number of those examined with verification of the diagnosis in the oncological institution was 596. The proportion of correct diagnoses was 94%. The total number of diagnostic errors that would occur in the absence of a true double scan accounted for 36 (6%) cases.Conclusion. The proposed screening method makes it possible to increase the breast cancer detection in the early preclinical stages of the disease, to provide the available diagnostics for the population due to mobile mammography complexes, and to speed up the process of diagnostics and further hospitalization for examination and necessary treatment according to the disease stage in a specialized oncological institution.